Analysis of a hybrid Android system for fall detection - Casilari-Pérez, Eduardo; Oviedo-Jiménez, Miguel Ángel (My University, 2016)
Android personal devices have become an interesting and cost-effective technology to deploy wearable Fall Detection Systems. In contrast with other smartphone-based solutions, this paper describes a fall detection architecture that integrates two-Bluetooth enabled devices: a smartwatch and a smartphone. The evaluation of the system under different fall recognition algorithms and mobility patterns indicates that the simultaneous operation of the two devices as fall detectors clearly improves the specificity of the system when compared to the cases where just one device is employed as a fall detector. The performed analysis also encompasses the study of the battery consumption and the performance of the system under constant monitoring in everyday life conditions.
Keywords: Asistencia sanitaria; Tele-healthcare; Tele-monitoring; mHealth; Fall detection system; Smartphone; Smartwatch; Bluetooth